Third Neighbor Policy Concept in Mongolia’s Geopolitics - Sanallkhundev, Bayasgalan (Mongolian Journal of International Affairs, 2021)
Since the 1900s when Mongolia fought for its independence, it was looking for an ally or a supporter on which it could rely on. One of the options was third neighbor. During the dramatic times Mongolia tried to approach Japan, as the closest possible country to have relation, and the U.S. as a country somehow caught its attention, to establish, if not diplomatic, at least trade relation. Third neighbor policy is unique, as it is associated only with Mongolia due to its unique geographic location. Looking for third neighbor, it is important for Mongolia to maintain balance between two big neighbors, and to have relationship with other developed countries. But the U.S. saw Mongolia not only as a young and a good example of democracy, and strategic partner, but also possible “ally” which lies between Russia and China. Third neighbor policy is not just an ordinary policy in foreign policy; it is a concept which is important for Mongolia, for a country which is sandwiched between two big nuclear Powers. With changing international environment Mongolia’s strategic importance never left behind. Here will be discussed that Mongolia’s third neighbor policy cannot be limited just with foreign policy or relationships with other countries. But it could have broader meaning from geo-strategic perspective, depending from international politics. I am arguing that third neighbor policy is more than just a foreign policy, it is a concept.